Palladium catalyst as well as preparation method and application thereof
By supporting atomic-level palladium on the WOx_C composite material to form a Pd/WOx_C catalyst, the high cost and stability problems of existing platinum-based catalysts are solved, and an electrocatalyst with high catalytic activity and stability is achieved, which is suitable for hydrogen production by electrolyzing water.
Patent Information
- Application Number
- CN202411716846.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The high cost, scarcity and prone to poisoning of existing platinum-based catalysts during the catalysis process limit their application in large-scale hydrogen production, and the traditional palladium atom synthesis method is complex, has poor stability and is not ideal catalytic activity.
The WOx_C composite material with a nanowire mesh structure is used as a support to prepare the WOx_C composite material through hydrothermal reaction, and atomic-level palladium is supported thereon to form a Pd/WOx_C catalyst.
Electrocatalysts with high catalytic activity and excellent stability are achieved, reducing production costs, and the main form of palladium is isolated single atoms, combining with strong interactions of the support, improving catalytic performance.
Smart Images

Figure CN119530865A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a palladium catalyst, a preparation method and application thereof. Background Art
[0002] The increasing severity of global fossil energy and environmental problems has prompted people to actively explore new sustainable and environmentally friendly alternative energy sources. Hydrogen (H2) is considered to have great application prospects in the field of future energy storage because it has the highest energy density among all fuels and water is the only by-product in the energy conversion process (zero carbon emissions).
[0003] Water electrolysis is considered a promising method for sustainable hydrogen production. Compared with methane steam reforming or coal gasification, it has many advantages: (1) The raw material is water, which is abundant on Earth; (2) The energy required for electrocatalysis can be obtained from renewable solar or wind energy; (3) No greenhouse gases or pollutants are produced during the electrocatalytic hydrogen production process; (4) High-purity H2 can be obtained from electrocatalytic hydrogen production (H2 and O2 are produced separately in the electrolyzer).
[0004] Electrocatalytic hydrogen evolution mainly involves the cathode hydrogen evolution reaction (HER) of water electrolysis. Currently, platinum (Pt)-based catalysts are the preferred electrocatalysts for HER, which have high current density and small Tafel slope. However, the high cost, scarcity and easy poisoning of Pt-based catalysts during the catalytic process limit their application in large-scale hydrogen production. Therefore, the development of low-cost, highly active and highly stable electrocatalysts is crucial to energy science.
[0005] Palladium (Pd) is the metal with the lowest melting point and the smallest density among the platinum group metals. It has similar properties to platinum metal in many aspects. It has significant catalytic ability and relatively abundant resource reserves, so it is considered to be one of the best substitutes for platinum catalysts. It is well known that palladium has a high affinity for hydrogen and its cost is lower than that of platinum catalysts. These have promoted the application of palladium-based nanomaterials in hydrogen storage, fuel cells, gas sensors / biosensors and organic coupling synthesis. The traditional synthesis of palladium atoms is mainly based on chloropalladic acid, palladium chloride and palladium nitrate, and is prepared by impregnation + high-temperature reduction in a hydrogen atmosphere. The synthesis method is complicated; the palladium atoms obtained by the traditional synthesis method have poor stability; in addition, its catalytic activity only comes from a small amount of atomic-level palladium metal on the surface, and the carrier material that occupies the main body does not effectively participate in the catalytic reaction, and the overall catalytic effect is not ideal.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a palladium catalyst, a preparation method and application thereof, aiming to provide an electrocatalyst with high catalytic activity and excellent stability.
[0008] The present invention is achieved in that:
[0009] In a first aspect, the present invention provides a palladium catalyst, comprising a carrier and palladium supported on the carrier; wherein the carrier is WO having a nanowire network structure. x _C composite materials.
[0010] In an optional embodiment, in the palladium catalyst, the mass fraction of palladium is 0.5wt%-3.0wt%; preferably 1.0wt%-2.0wt%;
[0011] Preferably, the palladium loaded on the carrier is at the atomic level. XAFS (X-ray absorption fine structure) and HAADF-STEM analysis results show that Pd 1.54 / WO x In _C 1:1, Pd mainly exists in the form of isolated single atoms and also contains a small amount of clusters.
[0012] In an alternative embodiment, in the preparation of WO x When preparing the composite material of _C, the mass ratio of the tungsten source to the carbon source is controlled to be 1:(0.5-2), preferably 1:(0.8-1.2).
[0013] In a second aspect, the present invention provides a method for preparing a palladium catalyst according to any one of the aforementioned embodiments, comprising: x _C composite material loaded with palladium.
[0014] In an optional embodiment, the method comprises: forming WO having a nanowire network structure x _C composite material and water are mixed to obtain a first mixed solution; a palladium source and water are mixed to obtain a second mixed solution, and the second mixed solution and the first mixed solution are mixed to react.
[0015] In an optional embodiment, the palladium source is selected from at least one of sodium chloropalladate, chloropalladic acid and palladium chloride; preferably sodium chloropalladate;
[0016] Preferably, WO x The mass ratio of the C composite material to the palladium source is 100:(0.1-100), more preferably 100:(2-8); further preferably 100:(3-5);
[0017] Preferably, in the first mixed solution, WO x _C The concentration of the composite material is less than or equal to 100 mg / mL;
[0018] Preferably, in the second mixed solution, the concentration of the palladium source is less than or equal to 100 mg / mL.
[0019] In an optional embodiment, the second mixed solution is added dropwise to the first mixed solution, stirred for 20 h-30 h, and then reacted at 50° C.-95° C. for 5 min-60 min.
[0020] In an alternative embodiment, WO x The preparation process of the _C composite material includes: mixing a tungsten source, a carbon source and a solvent, and then performing a hydrothermal reaction;
[0021] Preferably, the reaction temperature of the hydrothermal reaction is 150°C-250°C, and the reaction time is 3h-8h;
[0022] Preferably, cooling is performed after the hydrothermal reaction is completed, followed by solid-liquid separation, and the obtained solid material is washed and dried.
[0023] In an optional embodiment, the mass ratio of the tungsten source to the carbon source is 1:(0.5-2);
[0024] Preferably, the tungsten source is tungsten hexachloride;
[0025] The carbon source is glucose;
[0026] Preferably, the solvent is triethylene glycol.
[0027] In a third aspect, the present invention provides the use of any palladium catalyst in the aforementioned embodiments or a palladium catalyst prepared by any preparation method in the aforementioned embodiments in the electrolysis of water to produce hydrogen;
[0028] Preferably, the palladium catalyst is used to electrolyze water to produce hydrogen in an acidic medium.
[0029] The present invention has the following beneficial effects: the present invention uses WO with oxygen-rich vacancies having a nanowire network structure. x _C composite material is used as a carrier, and its strong adsorption and thermal reduction effects are used to strengthen the atomic-level palladium and WO x The palladium catalyst provided by the present invention has the advantages of adjustable atomic size, excellent catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 X-ray diffraction pattern;
[0032] Figure 2 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 paramagnetic resonance spectrum; a and b are both paramagnetic resonance spectra, but the conversion methods are different;
[0033] Figure 3 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 SEM image;
[0034] a, b means WO x ,c、d represent WO x _C 1:1, e and f represent Pd 1.60 / WO x , g and h represent
[0035] Pd 1.54 / WO x _C 1:1;
[0036] Figure 4 For Pd foil, Pd 1.54 / WO x Normalized XANES spectra of _C 1:1 and PdO at Pd K edge;
[0037] Figure 5 Pd foil, Pd1.54 / WO x _C 1:1 and PdO characterization diagram; a represents Pd foil, Pd 1.54 / WO x Pd R spatial spectra of EXAFS of _C 1:1 and PdO; b represents Pd foil, Pd 1.54 / WO x _C 1:1 and Pd k-space spectra of PdO; c represents Pd 1.60 / WO x HAADF-STEM images of Pd1.54 / WO x _C 1:1 HAADF-STEM image; f represents Pd 1.54 / WO x _C 1:1 HAADF-STEM-EDS mapping image;
[0038] Figure 6 Pd 1.54 / WO x _C 1:1 and Pd foil spatial fitting curve; a represents Pd 1.54 / WO x _C 1:1 EXAFS R spatial fitting curve; b represents Pd 1.54 / WO x _c represents the EXAFS k-space fitting curve of 1:1; c represents the EXAFS R-space fitting curve of Pd foil; d represents the EXAFS k-space fitting curve of Pd foil;
[0039] Figure 7 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 linear sweep voltammetry curve and Tafel slope; a represents the linear sweep voltammetry curve; b represents the Tafel slope;
[0040] Figure 8 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 stability test results; a represents WO x , b means WO x _C 1:1, c represents Pd 1.60 / WO x , d represents Pd 1.54 / WO x _C 1:1;
[0041] Fig. 9 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 chronoamperometry test results. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0043] In order to further reduce the cost of palladium-based catalysts and achieve the goal of commercial application, researchers have adopted various synthetic strategies to improve the utilization rate of precious metals and reduce the amount of precious metals used, such as alloying, hybridization, and shrinking nanoparticles to the atomic level. Among them, atomic-level catalysts are achieved by reducing the size of metal nanoparticles to nanoclusters or even single-atom levels, which is conducive to improving the atomic utilization rate of precious metal catalysts and reducing production costs in large-scale applications. However, the high surface free energy of atomic-level catalysts makes them prone to aggregation during material synthesis and catalytic reactions. Therefore, the selection and optimization of carriers in atomic-level catalysts are crucial, because the carrier affects the stability of the coordination environment of atomic-level catalysts. In addition, the metal atoms / clusters in atomic-level catalysts can also form an unsaturated coordination environment in atomic-level catalysts through strong interactions with the carrier, reducing the reaction barrier during the catalytic reaction and greatly improving the HER activity of the catalyst. At the same time, the strong interaction between the metal atoms / clusters and the carrier in the atomic-level catalyst leads to adjustable atomic and electronic structures, which further improves the catalytic performance of the atomic-level catalyst. It can be seen that the interaction between metal atoms / clusters and the local environment on the support is very important for designing high-performance atomic-level catalysts.
[0044] Based on this, the embodiment of the present invention designs a WO based on oxygen-rich defects. x _C nanowire network structure of atomic-scale Pd catalyst. Prepared Pd / WO x The Pd / WO catalyst exhibits excellent catalytic activity in acidic media and excellent stability at high current density. x _C catalysts will hopefully become suitable substitutes for Pt catalysts in acidic HER.
[0045] The present invention provides a method for preparing a palladium catalyst in a WO having a nanowire network structure. x _C composite material is loaded with palladium, the steps are as follows:
[0046] S1. Preparation of WO with nanowire network structure x _C Composite Materials
[0047] WO xThe preparation process of the _C composite material includes: mixing a tungsten source, a carbon source and a solvent, and then performing a hydrothermal reaction. After the hydrothermal reaction, the WO can be obtained by conventional separation and purification methods. x _C composite materials.
[0048] In some embodiments, the tungsten source is tungsten hexachloride, but not limited thereto; the carbon source is glucose, but not limited thereto. The above tungsten source and carbon source are suitable for the preparation method provided in the embodiment of the present invention to obtain uniform WO x _C composite material. The solvent is triethylene glycol, but not limited thereto.
[0049] Furthermore, the mass ratio of the tungsten source to the carbon source is 1:(0.5-2), such as 1:0.5, 1:0.8, 1:1.0, 1:1.3, 1:1.5, 1:1.8, 1:2.0, etc., preferably 1:(0.8-1.2). By adjusting the mass ratio of the tungsten source to the carbon source, the prepared WO x _C composite materials can better combine with palladium, improving the catalytic activity and stability of the composite catalyst.
[0050] In some embodiments, the reaction temperature of the hydrothermal reaction is 150°C-250°C, and the reaction time is 3h-8h. By adjusting the temperature and time of the hydrothermal reaction, a uniform WO having a nanowire network structure is prepared. x _C composite material. Specifically, the reaction temperature of the hydrothermal reaction can be 150°C, 180°C, 200°C, 230°C, 250°C, etc.; the reaction time can be 3h, 4h, 5h, 6h, 7h, 8h, etc.
[0051] Furthermore, after the hydrothermal reaction is completed, the reaction mixture is cooled, and then the solid-liquid separation is performed. The solid material obtained by the solid-liquid separation is washed and dried to remove the residual solvent and other materials on the surface. After drying, pure WO is obtained. x _C composite material. Specifically, WO can be collected by centrifugation. x _C nanowire network structure, then washed with anhydrous ethanol, and the obtained WO x _C The nanowire network was freeze-dried in a vacuum freeze dryer.
[0052] S2, palladium loading
[0053] WO with nanowire network structure x The _C composite material is mixed with water to obtain a first mixed solution; the palladium source is mixed with water to obtain a second mixed solution, the second mixed solution is mixed with the first mixed solution for reaction, and the palladium is uniformly loaded on the WO by heating the reaction. x _C composite material.
[0054] To achieve a better loading effect, the second mixed liquid is added dropwise to the first mixed liquid, stirred for 20h-30h, and then reacted at 50℃-95℃ for 5min-60min. After a long period of stirring, the raw materials are evenly mixed, and then the temperature is raised to react to achieve uniform loading of palladium. The second mixed liquid is slowly dispersed into the first mixed liquid. The slower the dispersion speed, the more conducive it is to the formation of atomic-level Pd. The long-term stirring is to achieve the initial stable loading of palladium ions. Then the temperature is raised to react, and the palladium ions are accelerated to be reduced to metallic palladium atoms by adjusting the reaction temperature, and the atomic-level palladium and WO are achieved. x The stable composite of _C nanowire network structure strengthens the interaction between palladium and the carrier and improves the stability of atomic-level palladium catalyst.
[0055] Specifically, the stirring time can be 20h, 23h, 25h, 28h, 30h, etc., the reaction temperature can be 50°C, 60°C, 70°C, 80°C, 90°C, 95°C, etc., and the reaction time can be 5min, 10min, 20min, 30min, 40min, 50min, 60min, etc.
[0056] In some embodiments, the palladium source is selected from at least one of sodium chloropalladate, chloropalladic acid and palladium chloride, and the palladium source can be any one or more of the above; preferably sodium chloropalladate, using sodium chloropalladate as the palladium source, the prepared composite catalyst has better catalytic performance and stability, which may be due to: in the process of synthesizing atomic-level palladium catalysts, sodium ions will participate in the synthesis reaction, and the joint action of palladium and sodium leads to better performance of the composite catalyst. The inventor has only found that sodium chloropalladate can obtain atomic-level palladium with excellent catalytic activity and adjustable size through this synthesis method, and the effects of using chloropalladic acid and palladium chloride are worse than those of sodium chloropalladate.
[0057] Furthermore, WO x The mass ratio of the WO composite material to the palladium source is 100:(0.1-100), preferably 100:(2-8); more preferably 100:(3-5). By optimizing the amount of the palladium source, the catalytic performance of the composite catalyst can be further improved. Specifically, WO x The mass ratio of the _C composite material to the palladium source can be 100:0.1, 100:0.5, 100:1.0, 100:2.0, 100:3.0, 100:4.0, 100:5.0, 100:8.0, 100:10, 100:30, 100:50, 100:80, 100:100, etc.
[0058] In some embodiments, when preparing the first mixed solution, ultrasonic dispersion or continuous stirring can be used to ensure that WO x _C nanowire network structure is completely dispersed in the aqueous solution. In the first mixed solution, WOx The concentration of _C composite material is less than or equal to 100 mg / mL, WO x The lower the concentration of the _C composite material, the better, and can be specifically 100 mg / mL, 90 mg / mL, 80 mg / mL, 70 mg / mL, 60 mg / mL, 50 mg / mL, 40 mg / mL, 30 mg / mL, 20 mg / mL, 10 mg / mL, 5 mg / mL, 1 mg / mL, etc.
[0059] In some embodiments, in the second mixed solution, the concentration of the palladium source is less than or equal to 100 mg / mL. Theoretically, the more water is used, the better, and the lower the concentration of sodium chloropalladate is, the better.
[0060] The present invention provides a palladium catalyst, comprising a carrier and palladium loaded on the carrier; wherein the carrier is WO having a nanowire mesh structure. x _C composite material, which can be prepared by the preparation method provided in the embodiment of the present invention. x The strong adsorption and thermal reduction of C nanowires strengthens the atomic-level palladium and WO x _C nanowire carrier, thus obtaining an atomic-scale palladium catalyst with adjustable atomic size, excellent catalytic activity and stability.
[0061] Furthermore, in the palladium catalyst, the mass fraction of palladium is 0.5wt%-3.0wt%; preferably 1.0wt%-2.0wt%, such as 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, etc. The palladium supported on the carrier is at the atomic level, and the XAFS (X-ray absorption fine structure) and HAADF-STEM analysis results show that Pd 1.54 / WO x In _C 1:1, Pd mainly exists in the form of isolated single atoms and also contains a small amount of clusters.
[0062] The palladium catalyst provided in the embodiment of the present invention can be used in the production of hydrogen by electrolysis of water, has good electrocatalytic performance, and is particularly suitable for the production of hydrogen by electrolysis of water in an acidic medium.
[0063] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0064] Chemical reagents and drugs required for the following examples: tungsten hexachloride (WCl6), triethylene glycol (C6H 14 O4), glucose (C6H 12O6), isopropanol (C3H8O), sodium chloropalladate (Na2PdCl4), and 5.0wt% naphthol solution were purchased from Sinopharm Chemical Reagent Co., Ltd. All drugs were analytically pure and used directly without further purification.
[0065] Example 1
[0066] This embodiment provides a method for preparing a palladium catalyst, the steps are as follows:
[0067] (1) Preparation of WO with nanowire network structure x _C Composite Materials
[0068] 0.8 g of tungsten hexachloride and 0.8 g of glucose were dispersed and dissolved in 80 mL of triethylene glycol. The homogeneous mixture was then hydrothermally reacted at 200 °C for 5 h. After cooling, WO was collected by centrifugation. x _C nanowire network structure, washed with anhydrous ethanol, and the obtained WO x The nanowire network structure was freeze-dried in a vacuum freeze dryer. The obtained materials were named WO x _C 1:1.
[0069] (2) Loading palladium
[0070] 100 mg of WO x _C was ultrasonically dispersed into 100 mL of deionized water at a ratio of 1:1 to form a mixed solution A. In addition, 4 mg of sodium chloropalladate was dispersed and dissolved in 50 mL of deionized water to obtain solution B. Solution B was slowly added dropwise to solution A and stirred for 24 h. Then, the obtained mixture was heated to 90 ° C in a water bath and kept warm for 30 min. After cooling, the composite catalyst was collected by centrifugation, washed with anhydrous ethanol, and the obtained composite catalyst was freeze-dried in a vacuum freeze dryer to obtain Pd / WO x _C nanowire network structure catalyst.
[0071] The composition of the composite palladium catalyst obtained in Example 1 was tested by ICP-OES. The Pd content in the catalyst was 1.54 wt %. The corresponding catalysts were named Pd 1.54 / WO x _C.
[0072] Example 2
[0073] The only difference from Example 1 is that the amount of sodium chloropalladate used in step (2) is 2 mg.
[0074] The composition of the composite palladium catalyst obtained in Example 4 was tested by ICP-OES. The Pd content in the catalyst was 0.72 wt %. The corresponding catalysts were named Pd0.72 / WO x _C.
[0075] Example 3
[0076] The only difference from Example 1 is that the amount of sodium chloropalladate used in step (2) is 8 mg.
[0077] The composition of the composite palladium catalyst obtained in Example 4 was tested by ICP-OES. The Pd content in the catalyst was 2.89 wt %. The corresponding catalysts were named Pd 2.89 / WO x _C.
[0078] Example 4
[0079] The only difference from Example 1 is that the amount of glucose used in step (1) is 0.4 g, and the obtained materials are named WO x _C 2:1.
[0080] Example 5
[0081] The only difference from Example 1 is that the amount of glucose used in step (1) is 1.6 g, and the obtained materials are named WO x _C 1:2.
[0082] Example 6
[0083] The only difference from Example 1 is that in step (2), sodium chloropalladate is replaced by chloropalladic acid.
[0084] Example 7
[0085] The only difference from Example 1 is that in step (2), sodium chloropalladate is replaced by palladium chloride.
[0086] Example 8
[0087] The only difference from Example 1 is that in step (2), sodium chloropalladate is replaced by chloroplatinic acid.
[0088] Example 9
[0089] The only difference from Example 1 is that in step (2), sodium chloropalladate is replaced by ruthenium chloride.
[0090] Comparative Example 1
[0091] In this comparative example, tungsten oxide (WO x ) nanowires, WO was synthesized by a simple one-step and high-yield solvothermal method using tungsten hexachloride and triethylene glycol as tungsten precursor and solvent, respectively. xThe specific steps are as follows: 0.8 g of tungsten hexachloride was dissolved in 80 ml of triethylene glycol. Then the homogeneous mixture was hydrothermaled for 5 hours at 200°C. After cooling, WO was collected by centrifugation. x The nanowires were washed with anhydrous ethanol and freeze-dried in a vacuum freeze dryer.
[0092] Comparative Example 2
[0093] In this comparative example, tungsten oxide (WO x ) nanowires are loaded with palladium, and the specific steps are as follows: 100 mg of WO x Ultrasonic dispersion was performed in 100 mL of deionized water to form a mixed solution A. In addition, 4 mg of sodium chloropalladate was dispersed and dissolved in 50 mL of deionized water to obtain solution B. Solution B was slowly added dropwise to solution A and stirred for 24 h. Then, the obtained mixture was heated to 90 ° C in a water bath and kept warm for 30 min to obtain Pd 1.60 / WO x catalyst.
[0094] The composition of the composite palladium catalyst obtained by ICP-OES test of Comparative Example 2 was 1.60 wt %. The corresponding catalysts were named Pd 1.60 / WO x catalyst.
[0095] Comparative Example 3
[0096] This comparative example provides another method for synthesizing a single-atom palladium catalyst. x The specific steps are as follows: 1000 mg WCl6 and 30 mg Pd(O2CCH3)2 were dissolved in 10 mL ethanol. The above solution was continuously stirred and cooled in an ice bath for 2 h to uniformly distribute the palladium into the tungsten oxide matrix. A mixed solution of 0.5 mL deionized water and 10 mL ethanol was prepared in a separate vial. The W and Pd precursors were then mixed with the ethanol-water mixture to form a solution. The precipitate was then collected by centrifugation, washed with water, and dried at 60 °C for 12 h. The synthesized Pd / WO 3-x The powder was thermally annealed at 400°C with 5% H2 / Ar or Ar.
[0097] Test Example 1
[0098] The WO obtained in Example 1 and Comparative Examples 1-2 x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x_C 1:1 test:
[0099] X-ray diffraction pattern Figure 1 As shown, it can be seen that WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x The main characteristic peaks of _C 1:1 are located at ∼23.88° and 48.25°, corresponding to W 18 O 49 (JCPDS No.05-0393) (010) and (020) planes. In addition, Pd 1.60 / WO x The characteristic peak at 40.49° can be attributed to the (111) crystal plane of Pd particles (JCPDS No. 46-1043). 1.60 / WO x Compared with the XRD results of Pd 1.54 / WO x No characteristic peaks of Pd particles were observed in _C 1:1, indicating that Pd 1.54 / WO x The Pd species in _C 1:1 exist in the form of ultrafine particles (single atoms / clusters), which can prove that the carbon-modified oxygen-deficient tungsten oxide nanowire network structure can effectively realize the stable loading of atomic-level palladium metal. x In comparison, WO x _C1:1, Pd 1.60 / WO x and Pd 1.54 / WO x The characteristic peak of tungsten oxide in _C 1:1 has a significant blue shift, and the degree of blue shift is: Pd 1.54 / WO x _C 1:1>WO x _C 1:1>Pd 1.60 / WO x >WO x This means that the modification of carbon and palladium has increased the lattice spacing of tungsten oxide, optimizing the atomic structure and electronic structure of tungsten oxide, which is beneficial to the improvement of the HER performance of the catalyst.
[0100] Paramagnetic resonance spectroscopy Figure 2 As shown, it can be seen that WO x _C 1:1 and Pd 1.54 / WO x The oxygen vacancy intensity in _C 1:1 is higher than that in WO x and Pd1.60 / WO x The oxygen vacancy intensity in WO is much higher, and the introduction of atomic-scale Pd species makes WO x The oxygen defect concentration in _C 1:1 further increases, which indicates that both carbon and atomic-level Pd species have optimized the atomic and electronic structures of tungsten oxide, which has a positive effect on improving its HER performance.
[0101] SEM images are shown in Figure Figure 3 As shown, it can be seen that Figure 3 The original WO x The morphology of the nanowires is agglomerated, and abundant nanowire bundles can be observed from the magnified SEM images ( Figure 3 b). Interestingly, in WO x A unique nanowire network structure was observed in _C 1:1 ( Figure 3 cd), and the original WO x In comparison, WO x _C 1:1 nanowire network structure is more loose and no agglomerates are found.
[0102] Test Example 2
[0103] Characterization of the composite catalyst:
[0104] Figure 4 For Pd foil, Pd 1.54 / WO x Normalized XANES spectra of _C 1:1 and PdO at the Pd K edge show that Pd 1.54 / WO x The intensity of the white line of _C 1:1 is between that of Pd foil and PdO, which means that the valence state of Pd is lower than divalent, indicating that Pd in the catalyst 2+ and Pd 0 Exist at the same time.
[0105] Figure 5 For Pd foil, Pd 1.54 / WO x _C 1:1 and PdO characterization diagram; a represents Pd foil, Pd 1.54 / WO x Pd R spatial spectra of EXAFS of _C1:1 and PdO; b represents Pd foil, Pd 1.54 / WO x _C 1:1 and Pd k-space spectra of PdO; c represents Pd 1.60 / WO x HAADF-STEM images of Pd 1.54 / WO x_C 1:1 HAADF-STEM image; f represents Pd 1.54 / WO x _C 1:1 HAADF-STEM-EDS mapping image. Figure 5 The EXAFS (Extended X-ray Absorption Fine Structure) data in ab show that in the Pd foil The peak corresponds to the metallic Pd-Pd bond. The peak at corresponds to the Pd-O bond. 1.54 / WO x _C 1:1 in both and The characteristic peaks were observed at 1.54 / WO x In the 1:1 ratio of WO to Pd, single atoms and nanoparticles coexist. Moreover, the signal of the metal Pd-Pd bond is much weaker than that of the Pd-C / O bond. Combined with the analysis of XRD and SEM (in the case of oxygen-rich WO x No obvious Pd particles were observed on the 1:1 support. x The Pd on the _C 1:1 support exists mostly in the form of single atoms, accompanied by the generation of a certain amount of atomic-scale Pd nanoclusters. Based on this, HAADF-STEM was used to further verify the Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 in the form of Pd species. Figure 5 Medium c, Pd 1.60 / WO x HAADF-STEM images of WO x A large number of ultrafine nanoparticles different from tungsten oxide appeared at the edge of the nanowire. x There is no carbon element in the nanoparticles, and these ultrafine nanoparticles can be attributed to the nanoparticles of Pd. 1.60 / WO x The XRD characterization results are consistent with those of 1.54 / WO x _C 1:1 HAADF-STEM image ( Figure 5 No Pd 1.60 / WO x Similar edge features, which show amorphous edge features, are caused by the superior carbon doping modification. x A small number of bright spots also appeared at the edge of _C 1:1. Considering that the number of Pd atoms is much larger than that of C atoms, these bright spots may be produced by single Pd atoms. 1.54 / WO x _C 1:1 HAADF-STEM-EDS mapping image ( Figure 5 The test in f) further proves the uniform dispersion of W, O, and Pd at the atomic scale, and most of the Pd element is presented in the form of element mapping of isolated single atoms, including a small amount of element mapping of Pd clusters. Combined with the analysis results of EXAFS, it can be fully proved that Pd 1.54 / WO x The Pd in _C 1:1 exists mainly in the form of single atoms and also contains a small amount of clusters.
[0106] Figure 6 Pd 1.54 / WO x _C 1:1 and Pd foil spatial fitting curves. The accuracy of XANES and EXAFS fitting data was verified.
[0107] Test Example 3
[0108] Performance test of composite catalyst:
[0109] Figure 7 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 linear sweep voltammetry curve and Tafel slope; a represents the linear sweep voltammetry curve; b represents the Tafel slope.
[0110] Figure 8 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x _C 1:1 stability test results, the linear sweep voltammetry curves before and after 10000 cyclic voltammetry cycles are compared. Test conditions: Cyclic voltammetry curve test in acidic electrolyte (0.50MH2SO4), from -0.5V vs.RHE to 0V vs.RHE, the scan rate is 100mV s -1 .
[0111] Fig. 9 For WO x , WO x _C 1:1, Pd 1.60 / WO x and Pd 1.54 / WO x_C 1:1 chronoamperometry test results.
[0112] like Figure 7 , Figure 8 and Fig. 9 As shown, the Pd / WO prepared in the embodiment of the present invention x _C catalyst exhibits excellent catalytic activity in acidic medium and excellent stability at high current density. 1.54 / WO x _C 1:1 catalyst at 10 mA cm -2 The overpotential of Pd is 19 mV vs. RHE, which is comparable to the HER activity of commercial Pt-based catalysts. 1.54 / WO x _C1:1 catalyst at an applied potential of 31 mV vs. RHE (current density: 200 mA cm -2 ) and in the 24-hour current-time curve test, the loss of current density is minimal.
[0113] Test Example 4
[0114] The catalytic performance of the catalysts obtained by testing the examples and comparative examples is shown in Table 1.
[0115] Test method: X-ray diffraction (XRD) spectra were obtained by a SmartLab-SE X-ray diffractometer (using Cu Kα radiation). ). The palladium content was analyzed using ICP-OES (inductively coupled plasma emission spectrometer, ICAP7000, ThermoFisher, USA). The morphology and composition were observed by scanning electron microscopy (SEM, ZEISS Sigma 300FE-SEM), transmission electron microscopy (TEM; JEM-1400TEM at 100 kV and JEM-2100HRTEM at 200 kV), and high-angle annular dark field scanning electron transmission microscopy (HAADF-STEM; Cs CETCOR Image Corrector TEM / STEM, Spectra 300). Electrochemical measurements were performed using a CHI 760E electrochemical station. Data reduction, data analysis, and EXAFS fitting were performed according to standard procedures, using the ATHENA and ARTEMIS programs integrated in the Demeter software package. The energy calibration of the sample was performed using a standard Pd foil, which was measured simultaneously as a reference sample. For EXAFS modeling, the background behind the edge was subtracted from the overall absorption, normalized with respect to the edge-hopping step, and used a range of Hanning Program The Fourier transform is converted to real (R) space to obtain the k3-weighted EXAFS spectrum. The EXAFS of the Pd foil is fitted and the obtained amplitude reduction coefficient S0 is set in the EXAFS analysis. 2 value (0.778) to determine the coordination number in the scattering path of Pd single atoms in the sample.
[0116] The electrocatalytic performance test was carried out using a three-electrode system. Graphite rod, Hg / HgO electrode and glassy carbon electrode (glassy carbon disk with a diameter of 5 mm) were used as the counter electrode, reference electrode and working electrode of the three-electrode system, respectively. Preparation of ink: 5 mg of catalyst and 5 mg of carbon black were ultrasonically treated and dispersed in isopropanol (2000 μL) containing 40 μL of 5wt% naphthol solution. Then 20 μL of ink was dropped on the polished glassy carbon electrode, and the catalyst loading on the working electrode was 0.2 mg cm -2 All measurements were performed in an acidic aqueous solution (0.50 M H2SO4, pH = 0). Before the electrochemical test, the working electrode was activated by CV scanning (scanning range: -0.7 V vs. RHE-0 V vs. RHE) in a 0.50 M H2SO4 aqueous solution until a stable CV curve was obtained. Then a linear sweep voltammetry test (LSV) was performed between 0 V vs. RHE and -0.1 V vs. RHE. In addition, the working electrode was activated by CV scanning (scanning range: -0.7 V vs. RHE-0 V vs. RHE) in a 0.50 M H2SO4 aqueous solution at 100 mV s -1 The scan rate was changed between -0.5 V vs. RHE and 0 V vs. RHE for 10 000 cycles to test the stability. The stability of the prepared catalyst was then tested by chronoamperometry, and the initial current of the catalyst was maintained at 200 mA cm -2 .
[0117] Table 1 Catalytic performance test results of catalysts obtained in Examples and Comparative Examples
[0118]
[0119]
[0120] "--" in the table means not detected
[0121] From Table 1, we can see that Pd / WO x _C has the lowest overpotential and Tafel slope as well as the lowest capacity decay under acidic conditions, indicating that it has the highest HER activity and stability.
[0122] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A palladium catalyst, characterized in that The invention comprises a carrier and palladium loaded on the carrier; wherein the carrier is WO having a nanowire mesh structure. x _C composite materials.
2. The palladium catalyst according to claim 1, characterized in that In the palladium catalyst, the mass fraction of palladium is 0.5wt%-3.0wt%; preferably 1.0wt%-2.0wt%; Preferably, the palladium loaded on the carrier is at the atomic level.
3. The palladium catalyst according to claim 1 or 2, characterized in that In preparing the WO x When preparing the composite material of _C, the mass ratio of the tungsten source to the carbon source is controlled to be 1:(0.5-2), preferably 1:(0.8-1.2).
4. A method for preparing a palladium catalyst according to any one of claims 1 to 3, characterized in that: Including: WO with nanowire network structure x _C composite material loaded with palladium.
5. The preparation method according to claim 4, characterized in that: Including: WO with nanowire network structure x _C composite material and water are mixed to obtain a first mixed solution; a palladium source and water are mixed to obtain a second mixed solution, and the second mixed solution and the first mixed solution are mixed to react.
6. The preparation method according to claim 5, characterized in that: The palladium source is selected from at least one of sodium chloropalladate, chloropalladic acid and palladium chloride; preferably sodium chloropalladate; Preferably, WO x The mass ratio of the C composite material to the palladium source is 100:(0.1-100), more preferably 100:(2-8); further preferably 100:(3-5); Preferably, in the first mixed solution, WO x _C The concentration of the composite material is less than or equal to 200 mg / mL; Preferably, in the second mixed solution, the concentration of the palladium source is less than or equal to 200 mg / mL.
7. The preparation method according to claim 6, characterized in that: The second mixed solution was added dropwise to the first mixed solution, stirred for 20 h-30 h, and then reacted at 50° C.-95° C. for 5 min-60 min.
8. The preparation method according to claim 4, characterized in that: WO x The preparation process of the _C composite material includes: mixing a tungsten source, a carbon source and a solvent, and then performing a hydrothermal reaction; Preferably, the reaction temperature of the hydrothermal reaction is 150°C-250°C, and the reaction time is 3h-8h; Preferably, cooling is performed after the hydrothermal reaction is completed, followed by solid-liquid separation, and the obtained solid material is washed and dried.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the tungsten source to the carbon source is 1:(0.5-2); Preferably, the tungsten source is tungsten hexachloride; The carbon source is glucose; Preferably, the solvent is triethylene glycol.
10. Use of the palladium catalyst according to any one of claims 1 to 3 or the palladium catalyst prepared by the preparation method according to any one of claims 4 to 9 in the electrolysis of water to produce hydrogen; Preferably, the palladium catalyst is used to electrolyze water to produce hydrogen in an acidic medium.